The Combined Effect of Current Boosting and Power Loss on Photovoltaic Arrays under Partial Shading Conditions - Mas’ud, Abdullahi Abubakar (Engineering, Technology & Applied Science Research, 2023)
This study proposes a novel technique for improving the performance of photovoltaic (PV) arrays under Partial Shading Conditions (PSCs). A 4×4 solar PV array with 16 panels was considered. Bridge-Linked (BL), Total Cross-Tied (TCT), Honey Comp (HC), One Cross-Link (OCL), and Two Cross-Link (TCL) were among the topologies of interest. First, the combined effect of connecting switches and partial shading on the PV array was studied. Then, the power loss/gain caused by reconfiguring the PV array structure from Series-Parallel (SP) to other schemes was investigated. Finally, a method of boosting current into the PV array is proposed to reduce PSCs-related power losses in the connecting switches. The results show that the number of connecting switches in the topology plays an important role in determining power gain or loss at different partial shading levels. TCT and HC outperformed the others in terms of power improvement when PSCs were considered without current boosting. This is true for different levels of solar irradiation exposure. The SP topology is optimal when the solar irradiation level is greater than 900W/m2 or less than 200W/m2. TCT outperformed the others when the current was boosted in the PV array, with a power improvement of 108%, for certain PSCs.